Foreign direct investment of Polish enterprises in Ukraine – its conditions and structure - Kaczmarek Bogusław (Management)
The aim of the article is analysis (structure and direction of development) of Polish foreign direct investments in the Ukraine. The article consists of four parts: first shows the definition of FDI and some aspects and economic conceptions explaining the conditions of their undertaking by companies. The second part presents the economic situation of Ukraine as a country for FDI localization; the third part presents the legal and administrative conditions of business conditions in this country, and fourth shows the characteristics of FDI made in Ukraine by Polish entrepreneurs.